Isolation, selection, and biological characterization research of highly effective electricigens from MFCs for phenol degradation - Wei, Guo; Xia, Du; Li-Li, Wang; Hong, Yan (Folia microbiologica, 2018)
The microbial fuel cells (MFCs) are recognized to be highly effective for the biodegradation of phenol. For isolating the phenol-degrading bacteria, the sample containing 500 mg/L phenol was collected from the MFCs. The strain (WL027) was identified basing on the 16S rRNA gene analysis and phylogenetic analysis as Bacillus cereus. The effects of pH, temperature, concentrations of phenol, heavy metal ions, and salt on the growth of strain as well as the degradation of phenol have been carefully studied. The WL027-strain exhibited favorable tolerance for the metal cations including Cr2+, Co2+, Pb2+, and Cu2+ with the concentration of 0.2 mg/L and NaCl solution with a high concentration of 30 g/L. In 41 h, 86.44% of 500 mg/L phenol has been degraded at the initial pH at 6 and the temperature of 30 °C. The strain was highly active electrogenesis bacteria and the coulombic efficiency reached 64.25%, which showed significant advantage on the efficient energy conversion. Therefore, due to the highly efficient degradation of phenol, WL027-strain could be used in the treatment of phenol-containing wastewater.
Keywords: Biodegradation, Environmental; biodegradace; zdroje bioelektrické energie; Metals, Heavy; Bioelectric Energy Sources; Hydrogen-Ion Concentration; Temperature; fenol; fylogeneze; Bacteria; teplota; Phylogeny; těžké kovy; koncentrace vodíkových iontů; Phenol